2011
DOI: 10.1002/bjs.7462
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial of fibrin sealant to reduce postoperative drainage following elective lymph node dissection

Abstract: There was no advantage in using fibrin sealant during elective lymphadenectomy in terms of reducing drainage output or postoperative complication rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…Evidence in support of broad surgical application is inconclusive at present. A blinded, prospective, randomised controlled study (RCT) conducted on 74 patients undergoing elective axillary and groin lymph node dissections concluded that the use of fibrin glue to reduce drain output, duration of drainage or postoperative complications following elective axillary or inguinal lymphadenectomy cannot be justified . However, two randomised trials that investigated the use of fibrin sealant in tumour excision and axillary dissection for breast cancer in a total of 190 patients demonstrated a benefit in terms of drain output from the use of fibrin sealant .…”
Section: Discussionmentioning
confidence: 99%
“…Evidence in support of broad surgical application is inconclusive at present. A blinded, prospective, randomised controlled study (RCT) conducted on 74 patients undergoing elective axillary and groin lymph node dissections concluded that the use of fibrin glue to reduce drain output, duration of drainage or postoperative complications following elective axillary or inguinal lymphadenectomy cannot be justified . However, two randomised trials that investigated the use of fibrin sealant in tumour excision and axillary dissection for breast cancer in a total of 190 patients demonstrated a benefit in terms of drain output from the use of fibrin sealant .…”
Section: Discussionmentioning
confidence: 99%
“…The PRISMA flow chart is shown in Figure depicting the literature research results and study selection. Out of 1579 manuscripts screened for eligibility, six prospective randomized controlled trials were identified in the electronic databases meeting the eligibility criteria. Seven full‐text articles were excluded because they either did not meet inclusion criteria, the trial design was not suitable, a cointervention was performed or data was not yet published.…”
Section: Resultsmentioning
confidence: 99%
“…Two of the selected trials included patients for ILND exclusively . Four trials also examined ALND and reported the results collectively . In our study, 194 patients underwent ILND for inguinal lymph node positive malignant melanoma.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations